Neopterin levels and dexamethasone suppression test in posttraumatic stress disorder - Atmaca, M; Kuloglu, M; Tezcan, E; Onal, S; Ustundag, B (Springer Heidelberg, 2002)
Neopterin has recently gained growing importance as an immunological marker in psychiatric disorders. In the present study, we aimed to evaluate whether the dexamethasone suppression test (DST) and neopterin were associated with posttraumatic stress disorder (PTSD). Fourteen patients with PTSD and 14 controls were enrolled in the study. A clinical evaluation and measurements of cortisol and neopterin levels before and after DST were performed. Additionally, all patients were assessed by Clinician Administered PTSD Scale (CAPS). There was a significantly higher DST nonsuppression in the patient group than control group. There were positive correlations between the duration of illness and CAPS, basal cortisol or postdexamethasone cortisol levels in the patient group. The mean neopterin levels for both before and after DST were significantly lower in the patient group than control group. In conclusion, our results suggest that not only the patients with PTSD have considerable DST nonsuppression but also PTSD maybe associated with neopterin.
Keywords: PTSD; neopterin; DST; cortisol